1982
DOI: 10.1152/ajpregu.1982.242.3.r189
|View full text |Cite
|
Sign up to set email alerts
|

Muscle enzyme profile, diet, and flight in South American bats

Abstract: Activities of four catabolic enzymes (citrate synthase, hexokinase, 3-hydroxyacyl-CoA dehydrogenase, and phosphorylase) were measured in the pectoralis muscles of 10 species of South American bats, representing four families. The pattern of enzyme activities in these tissues suggests that these muscles differ qualitatively with other mammalian and avian muscles in two respects. First, the muscles of all 10 bat species were much more highly oriented toward fat metabolism and away from glucose metabolism than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…However, the present study suggests that these reserves may be important only for supplying the tissue itself, as observed by Yacoe et al(1982) in other bat species, and would probably depend on prolonged fasting conditions (i.e., 48 h). but under normal conditions, D. rotundus seems unable to store/mobilize large quantities of fat.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…However, the present study suggests that these reserves may be important only for supplying the tissue itself, as observed by Yacoe et al(1982) in other bat species, and would probably depend on prolonged fasting conditions (i.e., 48 h). but under normal conditions, D. rotundus seems unable to store/mobilize large quantities of fat.…”
Section: Discussionsupporting
confidence: 45%
“…besides lipids, other energy sources, e.g., glycogen and proteins, are also used by bats and other animals (freitas et al, 2003). However, studies on the enzyme profile of bats have reported that, in numerous species, including the neotropical phyllostomids, breast muscles present higher activity of lipid metabolic enzymes (Yacoe et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes involved in fatty acid oxidation generally show high levels of activity in bat flight muscles (Suarez et al, 2009;Yacoe et al, 1982), and HOAD and CPT activities have been reported to increase by 53% and 32%, respectively, during migration in hoary bats (McGuire et al, 2013b). The potential for fatty acid delivery via lipoproteins during migratory flight has not been studied in bats.…”
Section: Meeting the Challenge Of Fat-fueled Flightmentioning
confidence: 99%
“…The increased breast muscle glycogen concentrations observed in animals captured during the rainy season might be associated with the fact that the animals are using the nutrients from their diet to invest in flight, because this substrate in breast muscle is mainly used for energy expenditure by the muscle itself, as previously described for frugivorous and nectarivorous bats (Yacoe et al 1982;Welch et al 2008;Suarez et al 2009;Amitai et al 2010).…”
Section: Discussionmentioning
confidence: 71%